HE STRUCTURE OF CONGENITAL MALFORMATIONS OF THE FEMALE REPRODUCTIVE SYSTEM (ACCORDING TO THE TAJIK SRI OF OBSTETRICS, GYNECOLOGY, AND PERINATOLOGY) - F.B. AMINOVA; D.A. KHODZHAMURODOVA; F.O. KOSIMOVA; F.I. IBRAGIMOVA (Avicenna Tajik State Medical University, 2019)
Objective: To study the structure of congenital malformations of the reproductive organs in adolescent girls and women of early, and active reproductive age, according to their appeal to the Tajik Scientific Research Institute of Obstetrics, Gynecology, and Perinatology. Methods: 182 teenage girls and women of reproductive age (from 14 to 26 years), with isolated and combined congenital malformations of the reproductive organs and anomalies of the urinary system, were examined. All patients were: history collection (mothers and relatives), general clinical (general and gynecological) examination, abdominal cavity examination, rectum, vaginal probing, endoscopic (hysteroscopy, diagnostic and therapeutic laparoscopy) study, evaluation of the condition of the mammary glands according to the Tanner scale, hormonal screening, genetic and urologist consultation, determination of sex chromatin, echographic methods for examining the uterus and ovaries, magnetic resonance imaging of the pelvic organs. Results: In 29 (15.9%) patients noted different types of vagina malformations with impaired menstrual blood flow; congenital anomaly of the body and cervix were in 86 (47.3%) patients (saddle uterus - 43 (23.6%), two-horned uterus - in 23 (12.6%), single-horned uterus - 8 (4.4%), complete doubling of the uterus and cervix - in 7 (3.8%) and rudimentary functioning uterus - in 5 (2.7%) cases). Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome was detected in 22 (12.1%) patients, while in all cases female sex chromatin (46, XX) was diagnosed, 5 (2.7%) patients suffered from female false hermaphroditism and 4 (2.2%) - masculine false hermaphroditism. In 36 (19.8%) patients, genital malformations were combined with anomalies of the urinary system Conclusion: Identified various forms of congenital malformations of reproductive organs, clinically manifested with the onset of menarche, or - sexual life. In the structure of these defects, the developmental anomaly of the uterus and cervix prevailed over other congenital malformations and accounted for 47.3% of cases.